Analysis of the Impact of Product Innovation, Market Diversification, and Branding Strategies on Global Competitiveness through the Unique Value of Indonesian Palm Oil Exports - Judijanto, Loso; Rusdianto, Rusdianto; Desembrianita, Eva (Westscience Press, 2025)
This study examines the impact of product innovation, market diversification, and branding strategies on global competitiveness through the mediating role of unique value in Indonesian palm oil exports. Using a quantitative approach, data were collected from 150 respondents representing exporters, producers, government officials, and industry associations. A structured questionnaire employing a Likert scale (1–5) was used, and the data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results demonstrate that product innovation, market diversification, and branding strategies all have significant positive effects on unique value and global competitiveness. Furthermore, unique value is shown to play a partial mediating role, indicating that differentiation through sustainability, traceability, and product quality strengthens the effectiveness of these strategies. The findings highlight the necessity of shifting from a quantity-based to a value-based model of palm oil exports to secure Indonesia’s position in the global market. This study contributes both theoretically by extending competitiveness frameworks with unique value mediation and practically by offering strategic insights for policymakers and industry stakeholders.